Análise das produções literárias em Libras para crianças surdas: criação e repercussões dos materiais do #CasaLibras - Messias, Maria Emilia das Graças (Universidade Federal de São Carlos, 2025)
This article presents the results of a research project developed as an Undergraduate Thesis in the Bachelor's Degree in Brazilian Sign Language (Libras) and Portuguese Translation and Interpretation (TILSP) at the Federal University of São Carlos (UFSCar). The main objective of the study was to analyze the audiovisual productions of the #CasaLibras extension program, focusing on the identification of the most recurrent literary genres, the participation of the deaf community, and the main features of this digital repository aimed at deaf children and adolescents. The theoretical framework is grounded in Deaf Studies and the concept of deferred textuality, articulating discursive, visual, and linguistic aspects of Libras productions. The methodology involved a documentary analysis of 60 videos published on the project's YouTube channel, based on criteria such as literary genre, narrator profile, linguistic diversity, use of visual and audiovisual resources, and engagement data (views and interactions). To deepen the analysis, three videos with the highest number of views were selected and examined according to two analytical axes proposed by Martins (2024a; 2024b) through the Pedagogical Instrument for the Assessment of Libras Production – IPAS_Libras: (1) discursive-literary axis and (2) technical-linguistic axis. The results highlight the diversity of genres found in the productions — such as short stories, fables, jokes, and songs — and underscore the relevance of these media resources in the process of literary literacy in Libras, both for deaf children and for students in training in the field of translation and interpretation. The study concludes that the #CasaLibras repository constitutes an important didactic-pedagogical tool, offering accessible, aesthetically qualified, and culturally meaningful materials. It is expected that this research will contribute to improving the training of Libras translators and interpreters, encouraging translation practices committed to the linguistic rights of deaf children and to the promotion of literature in Libras within educational contexts.
Analysis of literary productions in Libras for deaf children: creation and repercussions of the #CasaLibras materials
Keywords: Libras; Formação de tradutores e intérpretes de Libras; Literatura surda; #CasaLibras; LINGUISTICA, LETRAS E ARTES::ARTES; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL